Origin of the alkali tonsteins from southwest China: Implications for alkaline magmatism associated with the waning stages of the Emeishan Large Igneous Province. Issue 1 (2nd January 2016) - Zhao, L.; Graham, I.
ABSTRACT: A unique type of Nb–Zr–REE–Ga-enriched alkali tonstein of pyroclastic origin occurs exclusively within the late Permian coal measures of southwest China. The alkali tonsteins are located within the lowest Xuanwei or Longtan formations of Wuchiapingian age, indicating that their age is later than the main episode of Emeishan Large Igneous Province (ELIP) magmatism. The alkali tonsteins have intermediate–felsic Al2 O3 /TiO2 values (12.6–34.2, mean 22.0), light rare earth element-enriched chondrite-normalised patterns, negative δEu and incompatible element ratios similar to those of ELIP alkaline Nb–Ta-enriched syenites. All available evidence shows that the alkali tonsteins from southwest China originated from coeval ELIP alkaline magmatism. The enrichment of Nb–Zr–REE–Ga in alkali tonsteins is derived from the ELIP alkaline Nb–Ta-enriched volcanic ashes and may represent the last stage of mineralisation associated with the Emeishan mantle plume activity.